Oxidative markers in cryopreservation medium from frozen-thawed embryos: a possible tool for improved embryo selection in in vitro fertilization? - Wiener-Megnazi, Zofnat (J Assist Reprod Genet, 2016)
PURPOSE: The present study evaluated the association between oxidative parameters in embryo cryopreservation medium and laboratory and clinical outcomes. METHODS: This prospective laboratory study was conducted in an IVF unit in a university-affiliated hospital with 91 IVF patients undergoing a frozen-thawed embryo transfer cycle. Following thawing, 50 μL of embryo cryopreservation medium was retrieved from each cryotube and tested by the thermochemiluminescence (TCL) assay. TCL amplitudes after 50 (H1), 150 (H2), and 280 s (H3) were recorded in counts per second (CPS) and the TCL ratio determined for comparison with implantation and pregnancy rates. RESULTS: A total of 194 embryos were transferred in 85 frozen-thaw cycles. Twenty-one pregnancies (24.7 %) occurred. Implantation and overall and clinical pregnancy rates were higher when the median TCL H1 amplitude was <32 CPS compared to ≥32 CPS (14.6 vs. 5.3 %, 37.5 vs. 17 %, 28.1 vs. 9.4 %, respectively). No pregnancies occurred when the H1 amplitude was ≥40 CPS. Logistic regression multivariate analysis found that only the median TCL H1 amplitude was associated with the occurrence of pregnancy (OR = 2.93, 95 % CI 1.065–8.08). The TCL ratio inversely correlated with the duration of embryo cryopreservation (r = −0.37). CONCLUSIONS: The results indicate that thawed embryos may express oxidative processes in the cryopreservation medium, and higher oxidative levels are associated with lower implantation rates. These findings may aid in the improved selection of frozen-thawed embryos for IVF.